LiNbO₃ 강유전체를 이용한 MFISFET의 제작 및 특성 - 鄭焞元(Soon-Won Jung); 丘庚完(Kyung-Wan Koo) (전기학회 논문지 P권, 57(2), 2008)
- MFISFETs with platinum electrode on the LiNbO3/aluminum nitride/Si(100) structures were successfully fabricated and the properties of the FETs have been discussed. ID-VG characteristics of MFISFETs for linear region (that is, 0.1 V of the drain voltage) showed hysteresis loop with a counter-clockwise trace due to the ferroelectric nature of LiNbO3 films. A memory window (i.e., threshold voltage shift) of the fabricated device was about 2[V] for a sweep from -4 to +4[V]. The estimated field-effect electron mobility and transconductance on a linear region were 530[cm2/Vs] and 0.16[mS/mm], respectively. The drain current of 27[μA] on the "on" state was more than 3 orders of magnitude larger than that of 30[nA] on the "off" state at the same "read" gate voltage of 1.5[V], which means the memory operation of the MFISFET. KCI Citation Count: 0